THE DEVELOPMENT OF VIDEO-BASED INTERACTIVE LEARNING MEDIA TO TEACH SPEAKING SKILLS AT X GRADE STUDENTS OF SMK NU DONOMULYO - Nurul Izza Maulidiya; Istina Atul Makrifah; Tyas Alhim Mubarok (Wiralodra English Journal, 2023)
This study examines the process and results of the development of interactive video-based learning media to teach speaking skills to X-grade students. This research is an ADDIE model research and development. The sample of this research is X DKV SMK NU Donomulyo, which consists of 20 students. The data were gathered by using observation, unstructured interviews, questionnaires, and tests. The data were analyzed by using the manual formula for percentage and SPSS 25 version. The findings showed a positive result. The percentage of media expert validation reaches 92,5% which means “very valid”, then the percentage of material validation reaches 93,75% which means “very valid”. Meanwhile, the test obtains the N-Gain index which reaches 0,548 which means “average” or average significance. The total percentage of students’ satisfaction questionnaire reaches 81,25% that deems “good” and “valid”. In conclusion, interactive video-based learning media is ready to use by teachers as learning media. It is intended that other researchers would create interactive learning media that are video-based for various subjects and skills to assist active and participatory English learning in future studies.